VARIASI GENETIK PADA KOMBINASI UJI PROVENANS DAN UJI KETURUNAN Araucaria cunninghamii DI BONDOWOSO-JAWA TIMUR - Dedi Setiadi; Mudji Susanto (Jurnal Pemuliaan Tanaman Hutan, 2012)
A progeny test of Araucaria cunninghamii seedling seed orchard was established in 2008 at Bondowoso, East Java. Eighty open-pollinated families collected from six seed sources (Fak-fak, Jayapura, Serui, Wamena,  Manokwari and Queensland) were tested. The trial was designed as Randomized Complete Block Design (RCBD) comprised of 80 seedlots, 4 tree- line plots with 4 replications. The anitial spacing was 4 m x 2 m. The growth analysis at 5 years old was aimed to know performance of 6 seed sources.The result showed significant differences between families within seed source for both height and diameter growth. The average of height growth was 7,0 m and diameter was 5,1 cm. Indivual heritability estimates for height and diameter were 0.32 and 0.48 respectively while family heritability estimates for height and diameter wer 0.49 and 0.72 respectively. Genetic correlation between height and diameter was strong and positive (rg = 0.83).